Tetrasomic Recombination Is Surprisingly Frequent in Allotetraploid Arachis. Issue 4 (20th February 2015) - Leal-Bertioli, Soraya; Shirasawa, Kenta; Abernathy, Brian; Moretzsohn, Marcio; Chavarro, Carolina; Clevenger, Josh; Ozias-Akins, Peggy; Jackson, Scott; Bertioli, David
Abstract: Arachis hypogaea L. (cultivated peanut) is an allotetraploid (2 n = 4 x = 40) with an AABB genome type. Based on cytogenetic studies it has been assumed that peanut and wild-derived induced AABB allotetraploids have classic allotetraploid genetic behavior with diploid-like disomic recombination only between homologous chromosomes, at the exclusion of recombination between homeologous chromosomes. Using this assumption, numerous linkage map and quantitative trait loci studies have been carried out. Here, with a systematic analysis of genotyping and gene expression data, we show that this assumption is not entirely valid. In fact, autotetraploid-like tetrasomic recombination is surprisingly frequent in recombinant inbred lines generated from a cross of cultivated peanut and an induced allotetraploid derived from peanut's most probable ancestral species. We suggest that a better, more predictive genetic model for peanut is that of a "segmental allotetraploid" with partly disomic, partly tetrasomic genetic behavior. This intermediate genetic behavior has probably had a previously overseen, but significant, impact on the genome and genetics of cultivated peanut.